Inclusive education in the municipality of Sento Sé/BA: an analysis from multiple perspectives (Research, Society and Development, 2021)
Inclusive education worldwide is not recent if we look at its genesis from the Universal Declaration of Human Rights in the 1940s, however, in Brazil, only in 2015 the Brazilian Law of Inclusion was consolidated. This study is based on four guiding questions and aimed to identify which inclusive education policies are developed in the municipality, investigating what are the guidelines that support these policies, aiming to understand how the specialized educational care has been performed and the main challenges encountered. This is a qualitative-quantitative research, with exploratory, bibliographic, and field character. The findings indicate that there are inclusive education policies in the municipality, however, it is essential to invest even more in continuing education for teachers and specialized materials for the proper care of students with disabilities.